Side Null Analysis of the Main-Auxiliary Antenna Array for Noncooperative Interference Cancellation - ZheYu Li; JiaHao Zhang; YaXing Li; FangMin He; HongZhang Gao; Jin Meng (International Journal of Antennas and Propagation)
In interference cancellation, the null at the angle of arrival (AoA) of interference can suppress interference. However, due to the large spacing between array elements and the periodicity of the array, some small nulls at the angles of noninterference are formed inevitably. When the AoA of the desired signal is in these small nulls, they impair the effectiveness of interference cancellation by attenuating the desired signal. This paper proposes the concept of a side null to represent these nulls in the noninterference direction. And the cancellation ratio of the desired signal (SCR) is deduced to quantitatively characterize the side null. The spatial noncooperative interference cancellation model based on the main-auxiliary antenna array is established. Based on this, the SCR is derived to evaluate the amount of desired signal attenuation. Then the simulation, respectively, in two-dimensional plane and three-dimensional space, describes the side null visually. Moreover, the method of side null reduction is discussed by modulation of the array. Finally, the existence of side null and its influence on interference cancellation are verified through the experiments. The results of the simulation and experiment are in good agreement, and both support the theoretical analysis.